Screening of carrier materials to formulate Trichoderma harzianum based bio-fungicide against foot and root rot disease of tomato (Lycopersicon esculentum L.) (Bangladesh Journal of Agricultural Research, 2014)
Eight different organic matters were tested for their suitability as carrier materials to prepare Trichoderma harzianum based bio-fungicides for controlling foot and root rot disease of tomato caused by Sclerotium rolfsii. Four independent experiments were conducted and found that the carrier materials used singly or in combinations were suitable to prepare the bio-fungicides. Mixed use of carrier materials gave better results as compared to single ones. When wheat bran + rice bran, wheat bran + MOC+ rice bran, grasspea bran + rice bran, and grasspea bran +MOC+ rice bran were used as carrier materials. T. harzianum based bio- fungicides reduced seedling mortality of tomato by 20.33, 19.33, 24.33, and 19.34%, respectively. Treatment of soil with those biofungicides previously infested with S. rolfsii caused considerable increased in shoot and root growth of tomato. Based on the findings of investigation, the above mentioned carrier materials might be used to prepare T. harzianum based bio-fungicides. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20415 Bangladesh J. Agril. Res. 39(2): 197-209, June 2014